Translating poetry: into the experience of multilingualism - Nowak, Stéphane (Traduttologia e Traduzioni, vol. II: Identità linguistica - identità culturale, 2021)
How to translate multilingual poets, who place the concern for orality at the heart of their work? Based on the poems of Agrafiotis and Costa Monteiro, the article formulates some hypotheses on the practices of transcreation, linguistic hybridization, and etymological concerns allowing neologisms to be authorized. It is thus a question of translating the performative dimension of the poem.